Enhancing Nutraceutical Properties of Moringa: A Biotechnological Perspective - Faramayuda, Fahrauk; Riyanti, Soraya; Adely, Alyaa Muliahati (Sriwijaya Journal of Medicine, 2025)
Moringa oleifera Lam. is recognized for its versatile nutritional and medicinal benefits, largely attributed to its rich polyphenolic content, which includes bioactive compounds with significant antioxidant, anticancer, antimicrobial, and antidiabetic properties. This study addresses the gap in knowledge regarding the enhancement of phenolic compounds in Moringa leaves through innovative biotechnological methods. The primary objective is to analyze the extraction and quantification of polyphenols from Moringa leaves subjected to boiling and fermentation processes to produce kombucha. Using the Folin-Ciocalteu method, quantified the total polyphenol content, revealing that boiled Moringa leaves contained 67.66 ± 2.79 mg/g of polyphenols, while the resulting kombucha tea exhibited a higher concentration at 70.66 ± 2.79 mg/g. These findings demonstrate the potential of Moringa leaves as not only a dietary supplement but also as a functional ingredient in health-promoting beverages, such as kombucha. The implications extend to enhancing the nutritional value of plant-based diets and establishing Moringa as a sustainable antioxidant source. This research underscores the importance of advanced biotechnological approaches in optimizing extraction and cultivation methods, thus potentially increasing phenolic yields. By providing crucial insights into the functional applications of Moringa leaves, this study contributes to the broader fields of plant biotechnology and food science, encouraging further exploration into their health benefits and utility in promoting sustainable nutrition.